COMPARING SERUM CYSTATIN C AND SERUM CREATININE AS EARLY MARKERS FOR ACUTE RENAL DYSFUNCTION IN INTENSIVE CARE PATIENTS: A CASE-CONTROL ANALYSIS. - Bharti, Roli; Anand Sinha, (Student's Journal of Health Research Africa, 2024)
Background Acute renal dysfunction is a critical concern in intensive care units (ICUs) and is associated with increased morbidity and mortality. Early detection is essential, and serum biomarkers like cystatin C and serum creatinine have shown promise. This study aimed to assess their utility in identifying acute renal dysfunction. Methods A case-control study involving 960 ICU patients was conducted. Age and gender matching were ensured between control and case groups. Serum cystatin C and serum creatinine were evaluated and analyzed. Comparative and ROC curve analysis was performed to assess the biomarkers' relevance. Results The study found age and gender matching, validating the control-case group comparisons. Serum cystatin C consistently distinguished between groups, demonstrating its potential as an early marker. Comparative analysis and ROC curve analysis supported the relevance of these biomarkers. Cystatin C exhibited superior sensitivity and specificity. Conclusion Serum cystatin C and serum creatinine are valuable biomarkers for the early detection of acute renal dysfunction in ICUs. Their consistent differentiation between control and case groups highlights their significance in critical care settings. Recommendations These biomarkers should be routinely considered for early assessment of acute renal dysfunction in ICUs. Further research is warranted to refine them to assess acute renal dysfunction in ICUs early